Comparison of carbon isotope ratio measurement of the vanillin methoxy group by gc-irms and 13c-qnmr - Greule, Markus; Le, Phuong Mai; Meija, Juris; Mester, Zoltán; Keppler, Frank (Journal of the American Society for Mass Spectrometry, 2024)
Site-specific carbon isotope ratio measurements by quantitative 13C NMR (13C-qNMR), Orbitrap-MS, and GC-IRMS offer a new dimension to conventional bulk carbon isotope ratio measurements used in food provenance, forensics, and a number of other applications. While the site-specific measurements of carbon isotope ratios in vanillin by 13C-qNMR or Orbitrap-MS are powerful new tools in food analysis, there are a limited number of studies regarding the validity of these measurement results. Here we present carbon site-specific measurements of vanillin by GC-IRMS and 13C-qNMR for methoxy carbon. Carbon isotope delta (δ13C) values obtained by these different measurement approaches demonstrate remarkable agreement; in five vanillin samples whose bulk δ13C values ranged from −31‰ to −26‰, their δ13C values of the methoxy carbon ranged from −62.4‰ to −30.6‰, yet the difference between the results of the two analytical approaches was within ±0.6‰. While the GC-IRMS approach afforded up to 9-fold lower uncertainties and required 100-fold less sample compared to the 13C-qNMR, the 13C-qNMR is able to assign δ13C values to all carbon atoms in the molecule, not just the cleavable methoxy group.